Factors that influence exclusive breastfeeding in the Working Area of the Samboja Health Center - Yuni Ikawati; Andi Lis Arming Gandini; Nino Adib Chifdillah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Breast milk is the ideal nutrition for babies that contains nutrients that best suit the needs of babies and contains a set of protective substances to fight disease. Purpose: to know the factors that influence exclusive breastfeeding in the Working Area of the Samboja Health Center. Method: This type of research was analytic observational with a cross-sectional design for all mothers who had babies aged 6-12 months as many as 225 people with a total sample of 127 people using proportional random sampling. Measuring tool questionnaire. Chi square test data analysis. Results: Most of the mothers' knowledge was not good, namely 67.7%. The most support from health workers who did not support it was 52.8%. The participation of mothers in pregnant women's classes was mostly in pregnant women's classes, namely 53.5%. Conclusion: exclusive breastfeeding is influenced by knowledge, support from health workers, participation in classes for pregnant women related to exclusive breastfeeding.